Islamic Bank Safety Net Issues: The Regulatory Challenges for Cross Border Islamic Banking Transactions - Bhuiyan, Abul Bashar; Ismail, Abdul Ghafar; Islam, K. M. Anwarul; Noor, Abd Halim Mohd; Solaiman, Mohammad; Rahman, Mohammad Abdur (International Journal of Islamic Business & Management, 2020)
This paper aims to identify major regulatory challenges in the safety net for providing insurances to the depositors in the cross-border transaction over the world. The study found that Islamic banking is facing major challenges to issue appropriate rules and regulations for providing the right safety against the deposit of customers with a conventional counterpart base on the Islamic shariah principles. Especially in the area of “chartering or licensing function, prudential regulation and supervision, deposits in the central bank, intervention and resolution mechanisms and capital adequacy standard” for safety net issues of Islamic Bank. The study recommended that the policymakers need to pay heed in a deliberate and intentional way to solve the above regulatory issues to face the existing challenges for the smooth operation and bright prospect of the Islamic Banking sector in the future.JEL Classification Codes: G21, G24, L26, P51.